BAHASA HUKUM DALAM PUTUSAN PERKARA PIDANA (THE LEGAL LANGUAGE IN THE CRIMINAL CASE DECISION) - Usman Pakaya (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2017)
This research is regarding the application of legal language and the language generating aspects on the legal text in the criminal case decision. In this research, the researcher applied several supporting theories in order to elaborating and analyzing the issue in the criminal case decision, which among others: the legal language, structure of discourse, speech act, terminology, language variation, coherent and cohesion, and legal language characteristic. Whilst the methodology of research applied by the researcher is a qualitative methodology, this method is used to find out the scientific truth of the research object with more depth. For the purpose of this research, the researcher obtained the data research from the criminal case decision in Gorontalo’s civil court (IB), Boalemo’s civil court (IIA), and Pohuwato’s civil court (IIA). The selection of city and regency are being considered in order to see the representation of the data sources based on existing class division in the civil court. Furthermore the purpose of this research is to elaborate the legal language, the structure, speech act, terminology, language variation, coherent and cohesion, and the characteristic of the criminal case decision. The result of the research have shown that the criminal case decision are built by several element of language generating, which is include: structure of discourse, speech act, terminology, language variation, coherence and cohesion, and a specialized characteristic.ABSTRAKPenelitian ini tentang penggunaan bahasa hukum dan aspek-aspek pembangun bahasa dalam teks hukum putusan perkara pidana. Dalam penelitian ini, peneliti menggunakan beberapa teori pendukung di dalam menguraikan dan menganalisis persoalan putusan perkara pidana, di antaranya adalah bahasa hukum, struktur wacana, tindak tutur, pengistilahan, variasi bahasa, koherensi dan kohesi, serta karakteristik bahasa hukum. Sementara metodologi penelitian yang digunakan peneliti dalam penelitian ini adalah metode penelitian kualitatif, metode ini digunakan untuk menemukan kebenaran ilmiah dari sebuah objek penelitian secara mendalam. Untuk sumber data penelitian, peneliti memperolehnya dari putusan perkara pidana PN Kota Gorontalo (kelas IB), PN Kabupaten Boalemo (kelas IIA), dan PN Kabupaten Pohuwato (kelas IIA). Pemilihan wilayah kota dan kabupaten dipertimbangkan untuk melihat keterwakilan sumber data berdasarkan pembagian kelas pada Pengadilan Negeri. Lebih lanjut penelitian ini bertujuan mengelaborasi bahasa hukum, struktur, tindak tutur, pengistilahan, gaya bahasa, serta koherensi dan kohesi putusan perkara pidana. Adapun hasil penelitian menunjukan bahwa surat putusan perkara pidana dibangun dari beberapa unsur pembangun bahasa, yaitu struktur wacana, tindak tutur, pengistilahan, variasi bahasa, koherensi dan kohesi, serta karakteristik khas.